Performance of dual purpose cowpea varieties - Paul, C.P.; Singh, B.B.; Fatokun, C.A. (1988)
Thirty-two improved cowpea varieties were evaluated for their grain, fodder and leaf yields and to assess the effect of leaf picking before flowering on fodder and seed yields, in order to identify those suitable for dual purpose use. In one main plot treatment no picking was done, while in the other tender leaves were picked at weekly intervals, starting at 4 weeks after planting and terminating at 50% flowering. Thus, depe, nding upon maturity of the variety, 2 to 4 pickings were done. Grain and fodder yields were determined at crop maturity in both treatments. Leaf yield ranged from 1. 7 to 6.0 t/ha, with grain yield ranging from 0.4 to 1.3 t/ha and fresh fodder from 8.2 to 16.5 t/ha. Leaf picking reduced grain yield 17-51%, with a mean reduction of 28%. When leaves were not picked, the grain yield ranged from 0. 7 to 1.6 t/ha and fodder yield from 9.3 to 20.2 t/ha. The crude protein content in leaves ranged from 31.5 to 35.0% and crude fibre from 14.0 to 22.4%. TVx 1948-01 F appeared to be the best variety, yielding 4.9 t/ha leaf, 1.3 t/ha grain and 13.4 t/ha fodder, and suffered only 21% reduction in grain yield due to leaf picking. The leaves of TVx 1948-01 F contained 33.4% protein and 17.2% fibre.